مواقع التواصل الاجتماعي واختراق الخصوصية الثقافية للمجتمع الغرداوي - - بن دهينه بشرى; - قنو شيماء; د/ خديجة طبال (جامعة عمار ثليجي الاغواط, 2023)
جاءت دراستنا بعنوان مواقع التواصل الاجتماعي واختراق الخصوصية الثقافية للمجتمع الغرداوي - دراسة ميدانية على عينة من المجتمع الغرداوي- وانطلقت دراستنا من اشكالية: هل لموقع التواصل الاجتماعي دورا في اختراق الخصوصية الثقافية للمجتمع الغرداوي ؟ وهدفنا من خلال دراستنا بشكل عام الى التعرف على مواقع التواصل الاجتماعي ودورها في اختراق الخصوصية الثقافية للمجتمع الغرداوي، وتم الاعتماد على المنهج الوصفي التحليلي في دراستنا ومن اجل الوصول الى النتائج الميدانية تم الاعتماد على 20 فردا من المجتمع الغرداوي منهم 10 افراد من العرب و10 افراد من بني مزاب حيث اعتمدنا على اداة جمع البيانات المقابلة وبعد تحليلها توصلنا الى النتائج التالية: 1. المجتمع الغرداوي يتواصل مع ثقافات الاخرى رغم اختلاف الثقافات به الا ان افراد يتواصلون مع ثقافات اخرى عبر مواقع التواصل الاجتماعي. 2. مواقع التواصل الاجتماعي تخترق خصوصيات الثقافية وتكسب مستخدمها ثقافات جديده في عده مجالات . 3. مواقع التواصل الاجتماعي تتدخل في الخصوصية الثقافية للمجتمعات حسب رغبة مستخدمها لانهم هم من يشاركون ثقافاتهم الخصة عبر صفحات مواقع التواصل الاجتماعي الا نادرا ما يكون اختراق للخصوصية الثقافية من خلال تهكر واختراق حسابات مواقع التواصل الاجتماعي التي تحتوي على خصوصيات ثقافية لصاحبها. الكلمات المفتاحية: مواقع التواصل الاجتماعي – اختراق – الخصوصية الثقافية Study summary: Our study was titled Social Networking Sites and Penetrating the Cultural Specificity of the Al-Ghardawy Community - A Field Study on a Sample of the Al-Ghardawy Society - Our study started from a problem: Does the social networking site have a role in penetrating the cultural privacy of the Ghardawy community? Our aim, through our study in general, was to identify social networking sites and their role in penetrating the cultural specificity of the Al-Ghardawy community, and the analytical descriptive approach was relied upon in our study, and in order to reach the field results, 20 individuals from the Ghardawy community were relied on, 10 of whom were Arabs and 10 were Arabs. Bani Mazab, where we relied on the corresponding data collection tool, and after analyzing it, we reached the following results: 1. The Ghardawy community communicates with other cultures, despite the difference in cultures, but individuals communicate with other cultures through social networking sites. 2. Social networking sites penetrate cultural specifics and gain new cultures for its user in several fields. 3. Social networking sites interfere in the cultural privacy of societies according to the desire of their users because they are the ones who share their own cultures through the pages of social networking sites, but rarely is there a breach of cultural privacy through hacking and hacking social networking accounts that contain the cultural specifics of its owner. Keywords: social networking sites - penetration - cultural privacy
دراسة ميدانية على عينة من المجتمع الغرداوي